2019
DOI: 10.1073/pnas.1821372116
|View full text |Cite
|
Sign up to set email alerts
|

Distinct differences in the nanoscale behaviors of the twist–bend liquid crystal phase of a flexible linear trimer and homologous dimer

Abstract: We synthesized the liquid crystal dimer and trimer members of a series of flexible linear oligomers and characterized their microscopic and nanoscopic properties using resonant soft X-ray scattering and a number of other experimental techniques. On the microscopic scale, the twist–bend phases of the dimer and trimer appear essentially identical. However, while the liquid crystal dimer exhibits a temperature-dependent variation of its twist–bend helical pitch varying from 100 to 170 Å on heating, the trimer exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 30 publications
2
46
0
Order By: Relevance
“…This is indeed the only example of spontaneous chiral symmetry breaking known in a fluid in the absence of spatial order [25]. 11 Many experimental studies have claimed the existence of the N TB phase in a number nematogenic systems with various molecular motifs [26][27][28][29][30][31][32][33]. These studies agree in showing that the pitch of the modulated nematic structure, which indeed exhibits both chiralities, fall in the nanometric range.…”
Section: A Generalized Achiral Nematicsmentioning
confidence: 71%
See 1 more Smart Citation
“…This is indeed the only example of spontaneous chiral symmetry breaking known in a fluid in the absence of spatial order [25]. 11 Many experimental studies have claimed the existence of the N TB phase in a number nematogenic systems with various molecular motifs [26][27][28][29][30][31][32][33]. These studies agree in showing that the pitch of the modulated nematic structure, which indeed exhibits both chiralities, fall in the nanometric range.…”
Section: A Generalized Achiral Nematicsmentioning
confidence: 71%
“…For c 1 , c 2 , and d given by (26a), corresponding to the first family of uniform distortions obtained in Sec. II B, equation (32) reduces to the following three scalar linear equations,…”
Section: Heliconical Distortionsmentioning
confidence: 99%
“…[16] Ramou et al reported that the N TB phase can be induced in mixtures of conventionaln ematic and nonmesogenic dimers. [17] Besides liquid-crystal dimers, the N TB phase has also been observedi nb ent-core molecules, [5,[18][19][20] oligomers, [21][22][23][24][25] and polymers. [3,4,26] Although the majority of twist-bend nematogens developeds of ar are achiral,t here have been af ew reports on formation of the N TB phase based on chiral bentshaped molecules,i nw hicht he chirality is located in the mesogenic-arm core, [27,28] terminal chain, [29] or spacer.…”
Section: Introductionmentioning
confidence: 99%
“…By far the greatest number of twist-bend nematogens reported so far may be described as odd-membered liquid crystal dimers having a similar molecular curvature to CB7CB. However, the N TB phase has also been observed for rigid bent-core materials [24], a hybrid bent-core-calamitic dimer [25], trimers and tetramers [26][27][28][29], a hexamer [30], and main-chain polymers [31]. The common structural feature shared by all these molecular architectures is curvature, although this is not always uniform.…”
Section: Introductionmentioning
confidence: 98%